Three-dimensional motion tracking correlates with skill level in upper gastrointestinal endoscopy - Arnold, Sif H.; Svendsen, Morten B.; Konge, Lars; Svendsen, Lars B.; Preisler, Louise (Endoscopy, 2015)
Background and study aim: Feedback is an essential part of training in upper gastrointestinal endoscopy. Virtual reality simulators provide limited feedback, focusing only on visual recognition with no feedback on the procedural part of training. Motion tracking identifies patterns of movement, and this study aimed to explore the correlation between skill level and operator movement using an objective automated tool.Methods: In this medical education study, 37 operators (12 senior doctors who performed endoscopic retrograde cholangiopancreatography, 13 doctors with varying levels of experience, and 12 untrained medical students) were tested using a virtual reality simulator. A motion sensor was used to collect data regarding the distance between the hands, and height and movement of the scope hand. Test characteristics between groups were explored using Kruskal-Wallis H and Man-Whitney U exact tests. Results: All motion-tracking metrics showed discriminative ability primarily between experts and novices in specific sequences.Conclusion: Motion tracking can discriminate between operators with different experience levels in upper gastrointestinal endoscopy. Motion tracking can be used to provide feedback regarding posture and movement during endoscopy training.